Contrasting trends in short-lived and long-lived mesoscale eddies in the Southern Ocean since the 1990s. (9th March 2023) - Shi, Fei; Luo, Yiyong; Wu, Renhao; Yang, Qinghua; Chen, Ruiyi; Wang, Chuanyin; Lin, Yichen; Chen, Dake
Abstract: Mesoscale eddies play an important role in the transport of heat, carbon, and nutrients in the Southern Ocean. Previous studies have documented an increasing intensity of the Southern Ocean eddy field during recent decades; however, it remains unclear whether the mesoscale eddies with different lifetimes have different temporal variations. Using satellite altimeter observations from 1993 to 2020, we found that the increasing trend in the intensity of eddies is dominated by long-lived eddies (with lifetimes ⩾ 90 d), whose amplitude has increased at a rate of ∼2.8% per decade; the increase is concentrated downstream of topography. In contrast, short-lived eddies (with lifetimes < 90 d) do not appear to have a significant trend in their amplitudes since the early 1990s. An energy conversion analysis indicates that the increased baroclinic instabilities of the mean flows associated with topography are responsible for the amplitude increase of the long-lived eddies. This study highlights the need for a better understanding of the changes in mesoscale eddies owing to their importance in the transport of heat, carbon, and nutrients.